The Antimicrobial Activity of Cannabinoids - John A. Karas; Labell J. M. Wong; Olivia K. A. Paulin; Amna C. Mazeh; Maytham H. Hussein; Jian Li; Tony Velkov (MDPI AG, 2020)
A post-antibiotic world is fast becoming a reality, given the rapid emergence of pathogens that are resistant to current drugs. Therefore, there is an urgent need to discover new classes of potent antimicrobial agents with novel modes of action. Cannabis sativa is an herbaceous plant that has been used for millennia for medicinal and recreational purposes. Its bioactivity is largely due to a class of compounds known as cannabinoids. Recently, these natural products and their analogs have been screened for their antimicrobial properties, in the quest to discover new anti-infective agents. This paper seeks to review the research to date on cannabinoids in this context, including an analysis of structure-activity relationships. It is hoped that it will stimulate further interest in this important issue.